Privatization : trends and recent developments - Kikeri, Sunita (Policy research working paper, 2005)
"This paper takes stock of recent privatization trends, examines the extent to which government ownership is still prevalent in developing countries, and summarizes emerging issues for state enterprise reform going forward. Between 1990 and 2003, 120 developing countries carried out nearly 8,000 privatization transactions and raised